Putative founder effect of Arg338* AP4M1 (SPG50) variant causing severe intellectual disability, epilepsy and spastic paraplegia: Report of three families. Issue 3 (2nd December 2022) - Becker, Aurélie; Felici, Charlotte; Lambert, Laëtitia; de Saint Martin, Anne; Abi‐Warde, Marie‐Thérèse; Schaefer, Elise; Zix, Christian; Zamani, Mina; Sadeghian, Saeid; Zeighami, Jawaher; Seifi, Tahereh; Azizimalamiri, Reza; et al.
Abstract: Bi‐allelic variants affecting one of the four genes encoding the AP4 subunits are responsible for the "AP4 deficiency syndrome." Core features include hypotonia that progresses to hypertonia and spastic paraplegia, intellectual disability, postnatal microcephaly, epilepsy, and neuroimaging features. Namely, AP4M1 (SPG50) is involved in autosomal recessive spastic paraplegia 50 (MIM#612936). We report on three patients with core features from three unrelated consanguineous families originating from the Middle East. Exome sequencing identified the same homozygous nonsense variant: NM_004722.4( AP4M1 ):c.1012C>T p.Arg338* (rs146262009). So far, four patients from three other families carrying this homozygous variant have been reported worldwide. We describe their phenotype and compare it to the phenotype of patients with other variants in AP4M1. We construct a shared single‐nucleotide polymorphism (SNP) haplotype around AP4M1 in four families and suggest a probable founder effect of Arg338* AP4M1 variant with a common ancestor most likely of Turkish origin. Abstract : In this study we report three new unrelated patients from Middle‐East consanguineous families carrying the previously described NM_004722.4(AP4M1):c.1012C〉T homozygous nonsense variant. We describe their phenotype, and provide evidence that the subjects carrying this variant originate from a common ancestor.